2021
DOI: 10.1039/d0sm01179g
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of antimicrobial activity of differently-synthesized chitosan nanoparticles against bovine mastitis pathogens

Abstract: The greatest concern in dairy farming nowadays is bovine mastitis (BM), which results mainly from bacterial colonization of the mammary gland. Antibiotics are the most widely used strategy for its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…According to the literature data, nanoparticles such as silver [ 72 , 75 ], copper nanoparticles [ 72 , 75 ], zinc oxide nanoparticles [ 76 ], nanogels [ 4 ], and chitosan nanoparticles [ 77 , 78 ] have been reported to show positive results in bovine mastitis management. Such therapeutic techniques are gaining popularity as tools for managing S. aureus mastitis due to the antimicrobial activity, including antibiotic-resistant strains and antibiofim activity [ 4 ].…”
Section: Alternative Strategies—potential Solutionsmentioning
confidence: 99%
“…According to the literature data, nanoparticles such as silver [ 72 , 75 ], copper nanoparticles [ 72 , 75 ], zinc oxide nanoparticles [ 76 ], nanogels [ 4 ], and chitosan nanoparticles [ 77 , 78 ] have been reported to show positive results in bovine mastitis management. Such therapeutic techniques are gaining popularity as tools for managing S. aureus mastitis due to the antimicrobial activity, including antibiotic-resistant strains and antibiofim activity [ 4 ].…”
Section: Alternative Strategies—potential Solutionsmentioning
confidence: 99%
“…isolated from milk from cows with clinical mastitis and found that the antimicrobial capacity of the formulation was equal to or greater than conventional antibiotics [ 18 ]. Furthermore, in another study, it was proven that smaller particles of Qo NPs have better antimicrobial activity on the development of S. aureus and S. xylosus strains [ 19 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…The present situation in the field of bacterial infection inhibition calls for nanotechnology and nanoscience with antibacterial characteristics [6,7] . Primarily it has been observed that the effectiveness of antibacterial agents is greatly determined by their size [8,9] . The significant specific surface area of nanomaterials enables them to grab microbes and increases interaction with microbial membranes, which enhances the antibacterial characteristics of nanomaterials [10] .…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Primarily it has been observed that the effectiveness of antibacterial agents is greatly determined by their size. [8,9] The significant specific surface area of nanomaterials enables them to grab microbes and increases interaction with microbial membranes, which enhances the antibacterial characteristics of nanomaterials. [10] Additionally, nanomaterials have distinct physicochemical properties that can either completely deactivate microbes through interaction with the nanomaterials or through their catalytic processes which destroy the microbe.…”
Section: Introductionmentioning
confidence: 99%